Ação de fungicidas no controle da queima das folhas e nas características físico-química da cenoura cv. Nantes - Maringoni, Antonio Carlos [UNESP]; Baldini, Luiz Felipe Guedes [UNESP]; Demant, Luis Alfredo Rauer [UNESP]; Evangelista, Regina Marta [UNESP]; Fugita, Erika [UNESP] (My University, 2012)
The objective of present study is to evaluate the action of the fungicides mancozeb (Dithane NT – 3 Kg/ha), metiram (Polyram DF – 3 Kg/ha), azoxistrobin (Amistar WG – 100 g/ha), metiram + pyraclostrobin (CabrioTop – 2 Kg/ha) and pyraclostrobin (Comet – 400 mL/ha) in the control of leaf blight (Alternaria dauci), as well as their effects on some agronomical and physicalchemical parameters of the carrot cultivar Nantes. The plants were sprayed every seven days, starting 40 days after planting, and totaling five sprayings during their growing cycles. The severity of the disease was evaluated 45, 52, 59, 66, and 73 days after planting in order to determine the agronomical parameters (length, average diameter, and weight) and the physicalchemical characteristics (firmness, titratable acidity, soluble solids, sucrose and reduced sugars) of the roots. Applications of metiram + pyraclostrobin and pyraclostrobin, and this was found to be most effective in controlling the disease and on heavier carrot roots to pyraclostrobin. An increase in the level of soluble solids in the roots was observed with treatments of azoxistrobin, metiram + pyraclostrobin and pyraclostrobin. No effects were observed on the length, mean diameter, firmness, titratable acidity, and levels of sucrose and reduced sugars in the roots as a result of fungicide applications.

O presente trabalho teve por objetivo avaliar a ação dos fungicidas mancozeb (Dithane NT – 3 kg/ha), metiram (Polyram DF – 3 kg/ha), azoxistrobina (Amistar WG – 100 g/ha), metiram + piraclostrobina (CabrioTop – 2 kg/ha) e piraclostrobina (Comet – 400 mL/ha) no controle da queima das folhas (Alternaria dauci) e sobre alguns parâmetros agronômicos e físico-químicos da cenoura cultivar Nantes. Os produtos foram pulverizados a cada sete dias, a partir dos 40 dias após a semeadura (DAS), totalizando cinco pulverizações durante o ciclo da cultura. A severidade da doença foi avaliada aos 45, 52, 59, 66 e 73 DAS para determinação da área abaixo da curva do progresso de doença e por ocasião da colheita, aos 105 DAS, foram determinados os parâmetros agronômicos (comprimento, diâmetro médio e o peso) e físicoquímicos (firmeza, acidez titulável, sólidos solúveis, sacarose e açúcares redutores) das raízes. Foi constada maior eficácia no controle da doença para a aplicação de metiram + piraclostrobina e piraclostrobina e raízes mais pesadas para piraclostrobina. Houve incremento no teor de sólidos solúveis das raízes para os tratamentos azoxistrobina, metiram + piraclostrobina e piraclostrobina. Não foi constado efeito da aplicação dos fungicidas sobre o comprimento, diâmetro médio, firmeza, acidez titulável, teores de sacarose e de açúcares redutores das raízes.
Fungicide action in the control of leaf blight and the carrot cv. Nantes physical-chemical characteristics
Keywords: Daucus carota; Alternaria dauci; Fungicide; Post-harvest; Daucus carota; Alternaria dauci; Fungicida; Pós-colheita